Exploring How Silence Communicates - Dat Bao (Universitas Ahmad Dahlan, 2020)
This article argues that silence as communication can be academically practised in the classroom as much as talk, simply because talk and silence are both essential components of everyday interaction (Nakane, 2012). These two constructs are interdependent in the sense that one would not exist without the other. Silence can be practised in two different ways: one is to employ it as a mental processing process in learning; two is to observe and discuss how silence is used in communication. The article begins by sharing the literature review on how silence works in education, how it deserves a place in SLS theorisation, and how it constitutes communication competence. Secondly, it highlights classroom tasks that trigger silent processing and explain why this is the case. Thirdly, the discussion recommends an activity which addresses the value of silence, which was developed by the author through research and experience. Finally, there are recommendations for task design in which similar activity types are introduced to assist the learning of reflective students.